A randomized, placebo‐controlled phase I trial of live, attenuated herpes zoster vaccine in subjects with end‐stage renal disease immunized prior to renal transplantation. Issue 3 (25th March 2018) - Miller, Geraldine; Schaefer, Heidi; Yoder, Sandra; Miller, Rachel; Winokur, Patricia; Kotloff, Karen; Klassen, David; Wierzbicki, Michael; Amegashie, Cyrille; Edwards, Kathryn
Abstract: Background: Solid organ transplant recipients are at increased risk for reactivation of herpes zoster, or shingles, and have a higher frequency of serious complications including post‐herpetic neuralgia. A live, attenuated shingles vaccine is effective and approved for individuals 50 years and older. The vaccine is contraindicated following transplantation, but may be used in patients with renal failure. Utilization of the vaccine has been poor in patients with end‐stage renal disease, including those awaiting transplant, owing to concerns for safety, efficacy, and potential sensitization prior to transplant. Methods: We conducted a phase I, randomized, placebo‐controlled study of the safety and immunogenicity of live, attenuated Oka strain shingles vaccine in subjects prior to or awaiting renal transplant at 3 US centers. Subjects received vaccine a minimum of 4 weeks prior to transplant. Results: The vaccine was safe and well‐tolerated. There were no cases of herpes zoster or rash illness. There was no change in donor‐specific antibody or calculated panel reactive antibody after vaccination during the follow‐up period. There were no rejection episodes. There was a significant 2.1‐fold rise in geometric mean titer of anti‐VZV antibody at 5 weeks post‐vaccine. Conclusions: The data suggest that the shingles vaccine is safe in subjects with ESRD awaiting transplant. Antibody responses were similar to those seen previously in adults >50 years of age and are consistent with a protective response.